In Conflict and Custody : Therapeutic Counselling for Women - Shankardass, Rani Dhavan (New Delhi Sage Publications, 2012)
The book shows how therapeutic counselling can enable women in distress to take charge of their lives. It imparts theoretical and practical guidance for trainers and would-be counsellors to equip themselves better for therapeutic counselling of women with a range of social, legal and personal problems
Include Illustration, Reference and Index
Keywords: Women prisoners--Counseling of -- Women prisoners--Mental health -- India